PERGESERAN HAK PREROGATIF PRESIDEN PASCA AMANDEMEN UNDANG-UNDANG DASAR 1945 - Aspani, Budi (Solusi, 2020)
The President as the Head of State has prerogative rights besides having authority in outgoing relations contained in the 1945 Constitution. In the case of the formation, amendment and dissolution of state ministries after the 1945 Constitution Amendments do not become the full authority of the President, but are based on the law (Article 17 paragraph (4) of the 1945 Constitution), so that there will be no more unilateral dissolution of a state ministry by the President. The issues to be discussed are as follows: What has been changed in the amendment to the 1945 Constitution regarding the President's Prerogative Rights, and how the amendments to the 1945 Constitution on the President's Prerogative Rights on the government system in Indonesia. With the amendment of the 1945 Constitution four times, it has an influence on the position of the President in exercising his prerogative rights. The President's prerogative right before the amendment is not fully implemented to carry out the President's Constitutional obligations, but is related to political content. After the amendment to the 1945 Constitution there was a shift in the application of the President's prerogative rights, namely by including other state institutions in the implementation of the prerogative. Amendments to the 1945 Constitution on the President's Prerogative Rights did not result in a change in the Indonesian government system.